Teachers’ Well-Being, Emotions, and Motivation During Emergency Remote Teaching Due to COVID-19 - Panadero, Ernesto; Fraile, Juan; Pinedo, Leire; Rodríguez-Hernández, Carlos; Balerdi, Eneko; Díez, Fernando (Frontiers in Psychology, 2022)
This study explores the effects of the shift to emergency remote teaching (ERT) on teachers’ levels of well-being, emotions, and motivation. A total of 936 Spanish teachers participated in this nationwide survey from all educational levels, thus allowing comparison among levels, which is a novelty and strength of our study. Four aspects were explored: (1) instructional adaptation to ERT; (2) well-being changes and the main challenges in this regard; (3) changes in emotions; and (4) changes in motivation and the main factors. Importantly, we explored a number of teacher characteristics (e.g., gender, age) for the three last aspects. Our results show that teachers felt the impact of ERT on their well-being, emotions, and motivation. Additionally, female teachers, teachers with students of low socioeconomic status (SES), in public schools, and primary and secondary teachers were the most affected groups. This indicates that the impact of ERT differed and some populations of teachers are more at risk of suffering burnout because of ERT.